Peningkatan Hasil Belajar Kognitif Ilmu Pengetahuan Sosial Melalui Model Cooperative Learning Inside Outside Circle - Kartika Nurmala Dewi; Nedin Badruzzaman; Rais Hidayat (FKIP UNIVERSITAS PAKUAN, 2015)
The research is aimed at finding out the quality improvement and learning outcome of social science subject of the fifth grade students through Cooperative Learning Inside Outside Circle. The subjects of the research were the fifth grade students of an elementary school. There were 59 students with the composition of 28 males and 31 females. The study was conducted in the odd semester in 2015/2016. The research result shows that the learning outcome in the first cycle reached 70,48 or the percentage of passing grade was 46,55% while in the second cycle, it reached 78,62 or the percentage of passing grade was 84,48%; it means that the treatment was successful. For the quality of the learning, in the first cycle it reached 76%, and in the second cycle it was 86%. The observational result shows that students’ behavior improved. In the first cycle it reached 70%, while in the second it was 90%. Based on the research result above, it can be inferred that the implementation of Cooperative Learning Inside Outside Circle could improve the learning outcome of social science subject. Besides that, it could also improve the learning quality, students, participation and behavior.